Pengaruh Harga, Promosi, dan Kualitas Produk terhadap Keputusan Pembelian pada E-Commerce Lazada Indonesia - Maftuhah, Tatu; Raharjo, Joko S Dwi (NIAGARA Scientific Journal, 2024)
Consumer behavior is the basis for consumers to make purchasing decisions. The activity of thinking, considering and questioning goods before buying is or is included in consumer behavior. One of the consumer behaviors that is widely researched is the factors that encourage purchasing decisions. Several previous studies related to purchasing decision making obtained simultaneous positive results between price, promotion and product quality on consumer decisions in determining purchases. This article reviews several journals related to the correlation of purchasing decisions with perceptions of price, promotion and product quality, marketing management literature review. Based on the results of this research, it simultaneously shows that Price, Promotion and Product Quality influence Purchasing Decisions. Therefore, it is important for companies to understand consumer behavior. In order to determine marketing management to win the hearts of consumers. Keywords: Consumer Behavior, Price, Promotion, Product Quality, Purchasing Decisions